Profiling the Australian coaching workforce - Dawson, A.; Wehner, K.; Phillips, P.; Gastin, P.; Salmon, J (Deakin University, Centre for Exercise and Sports Scienece, 2013)
Sport coaching in Australia is undergoing unprecedented change at all levels of participation. The demand for the development of high quality coaches has emerged as a key issue for sport administrators and managers and yet we know little about the way Australian coaches work and develop themselves. As a coach and coach educator the following report on the Australian coaching workforce titled "Profiling the Australian Coaching Workforce" provides equal measures of comfort and alarm. It`s re-assuring to see the main reason we coach has not changed but the reasons coaches cite for discontinuing coupled with the high rate of coach drop-out across sports means we are not capitalising on their experience and expertise just when we need it most. This report is essential reading for sport policy makers, sport educators, sport researchers and coaches alike. (Forward)